The Dual Role of Cellular Senescence in Developing Tumors and Their Response to Cancer Therapy - Schosserer, Markus; Grillari, Johannes; Breitenbach, Michael (Frontiers in Oncology, 2017)
Cellular senescence describes an irreversible growth arrest characterized by distinct morphology, gene expression pattern and secretory phenotype. An important part of senescence research shows that the final or intermediate stages of senescence can be reached by different genetic mechanisms and in answer to different external and internal stresses. It has been maintained in the literature but never proven by clearcut experiments that the induction of senescence serves the evolutionary purpose of protecting the individual from development and growth of cancers. This hypothesis was recently scrutinized by new experiments and found to be partly true, but part of the gene activities now known to happen in senescence are also needed for cancer growth, leading to the view that senescence is a double-edged sword in cancer development. Also in current cancer therapy, cellular senescence is on the one hand intended to occur in tumor cells, as thereby the therapeutic outcome is improved, but might on the other hand also be induced unintentionally in non-tumor cells, causing inflammation, secondary tumors and cancer relapse. Importantly, organismic aging leads to accumulation of senescent cells in tissues and organs of aged individuals. Senescent cells can occur transiently, e.g. during embryogenesis or during wound healing, with beneficial effects on tissue homeostasis and regeneration, or accumulate chronically in tissues, which detrimentally affects the microenvironment by de- or transdifferentiation of senescent cells and their neighboring stromal cells, loss of tissue specific functionality and induction of the senescence-associated secretory phenotype, an increased secretory profile consisting of pro-inflammatory and tissue remodeling factors. These factors shape their surroundings towards a pro-carcinogenic microenvironment, which fuels the development of aging-associated cancers together with the accumulation of mutations over time. We are presenting an overview of the well-documented stress situations and signals, which can induce senescence. Among them, oncogene-induced senescence and stress-induced premature senescence are prominent. New findings about the role of senescence in tumor biology are critically reviewed with respect to new suggestions for cancer therapy leveraging genetic and pharmacological methods to prevent senescence or to selectively kill senescent cells in tumors.